Sediments Yields in Saimo Catchment of Tugen Hills in Baringo County, Kenya - Chesire, A. K.; Kollongei, J. K.; Ng’etich, W. (Africa Environmental Review Journal, 2022)
Soil erosion by water is one of the primary causes of land degradation and occurs throughout the world. Soil erosion contributes negatively to the already declining agricultural productivity thereby negatively impacting on people’s livelihoods and economic empowerment in Baringo County. There is need therefore, to understand the erosion processes and quantify sediment yield from catchments in order to propose technically viable, economically achievable and environmentally sustainable mitigation measures. This study focused on estimation of sediment yield from Tugen Hills particularly in Saimo catchment in Baringo County. Run-off plots measuring 5metres by 2metres with average slope of 17% were set up in the catchment, a bean crop was planted under three tillage treatments; conventional, mulching and control. These were done in triplicates in a randomized complete block design yielding nine run-off plots. Soil erosion parameters: run-off volume (Q) and peak flow rate (qp) were determined from the run-off plots in the catchment. Soil erodibility (K) was calculated mathematically based on soil samples collected and analyzed in the laboratory. Cover management (C) and support practice (P) factors were determined through observation and use of conversion tables. In terms of results, mean bulk densities for top soil and bottom soil were 1.05g/cm3 and 1.07 g/cm3 respectively meaning that low bulk densities for the top soil. The total value for fine sand and silt was 37.1%. The saturated hydraulic conductivity varied from 8.0 µm/s to 41.3 µm/s with a mean value of 24.1 µm/s. There were only two classes high and moderately high translating to code 2 and 3, respectively. Block three under no planting (control) had the highest percent cover (93%) towards the end of the growing season. The maximum sediments for each day had the highest value of 414 grams observed in block 2 with mulching. The MUSLE model did not accurately predict surface run-off and sediments yield compared to field data. Plots under cover crops had reduced soil erosion and lesser sedimentation yield. Future work is needed for new plots under different slopes.